2019
DOI: 10.3390/ijerph16173081
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Online CBT-I Intervention and a Face-to-Face Treatment for Shift Work Sleep Disorder: A Comparison of Sleep Diary Data

Abstract: In western societies, about one in six employees works in shifts. Shiftwork is associated with a number of poor somatic and psychological health outcomes, especially sleep issues. Higher rates of absenteeism and accidents in the workplace are possible consequences. Still, prevention programs and treatment options that are specifically tailored to shift-workers’ needs are rare. We devised a 4-week online cognitive behavioral therapy for insomnia (CBT-I) intervention (n = 21) and compared sleep outcomes to a fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 49 publications
1
42
1
1
Order By: Relevance
“…The main difference between the studied interventions appeared in the outcomes related to mental health. The gCBT-I of our study was effective in improving the mental health of shift workers, as also observed in earlier studies (Jarnefelt et al 2012;Okajima et al 2011;Peter et al 2019). The trait of worry had decreased substantially at 6-month follow-up, the interaction effect showing a larger reduction after the gCBT-I than SH control intervention.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The main difference between the studied interventions appeared in the outcomes related to mental health. The gCBT-I of our study was effective in improving the mental health of shift workers, as also observed in earlier studies (Jarnefelt et al 2012;Okajima et al 2011;Peter et al 2019). The trait of worry had decreased substantially at 6-month follow-up, the interaction effect showing a larger reduction after the gCBT-I than SH control intervention.…”
Section: Discussionsupporting
confidence: 88%
“…However, our previous non-randomized study showed no difference between the improvements among day and shift media workers after CBT-I (Jarnefelt et al 2014). In addition, a non-randomized study by Peter et al (2019) showed improvement in ISI among shift workers after online CBT-I. Regardless of the intervention, ISI improved moderately in our current study, and sleep-related dysfunctional beliefs along with burnout and stress symptoms showed small improvements lasting up to the 6-month follow-up after all three interventions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, improved SRI from week 1 to week 3 was associated with fewer naps. Data such as these have important implications for targeted therapies such as cognitive behavioral therapy for insomnia (CBT-I), which typically include reducing naps and/or sleep restriction as major components [38]. Such behavioral modifications could impact the SRI.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep medicine has come a long way due to increased public awareness, as highlighted by the study of Savic et al (2019), who reported that the nurses in their study had already adopted health-promoting coping strategies with their night shifts [32], including health practices of physical activity, healthy eating, engaging with social support and leisure, mindfulness, managing time, and work-related coping strategies. Nevertheless, the online platforms of mHealth [33] and cognitive behavioural therapy for insomnia (CBTi) [34] are resourceful, easily accessible materials for shift workers. Forest therapy (originating in the 1980s in Japan for stress reduction) that improved sleep efficiency in cancer patients [35] may be explored in shift workers in future studies.…”
mentioning
confidence: 99%